Examining the flexural behavior of honeycomb sandwich composites: A numerical and experimental study - Salwan AlHumairee; Ibtihal Mahmood; Mustafa Hunain; Hassan Raheem (Engineering and Technology Journal)
Composite sandwich panel structures have been widely used in engineering and aerospace applications. Predicting the flexural properties of theoretical composite constructions is crucial for efficiently designing sandwich composite panel products. This research investigates four different cell core forms—circular, hexagonal, rectangular, and triangular—utilized in the manufacture of sandwich composite structures using a numerical program. For each case, the sandwich composite panel structure maintained constant weight and constant thickness for all models. The skin was fabricated from one layer of carbon fiber and two layers of glass fiber, combined with 3% carbide silicon and 6% polysulfide rubber in an epoxy matrix. The volume fraction for both carbon fiber and glass fiber was 35%, embedded in the epoxy mixture containing polysulfide rubber and carbide silicon (SiC). Finite element analysis using ANSYS Workbench 17.2 under three-point bending tests of the models revealed the rectangular cell core form as the optimal choice, exhibiting the least distortion (0.42992 mm) compared to other forms. The circular, hexagonal, and triangular core forms demonstrated deformations of 0.47267 mm, 0.48254 mm, and 0.51483 mm, respectively, representing a 9.05%, 10.91%, and 16.5% increase in deformation compared to the rectangular core. The maximum elastic strain for the rectangular core was 0.0067369, while the circular, hexagonal, and triangular cores exhibited strains of 0.0098421, 0.0092298, and 0.0072145, respectively, showing a 31.55%, 27%, and 6.62% increase in strain compared to the rectangular core. From the results of the finite element analysis, the rectangular model was chosen for manufacturing experimental models. Three models were prepared according to the bending test requirements. The experimental results demonstrated strong agreement with the numerical findings of this study.